European transport simulator modeling of JET-ILW baseline plasmas: predictive code validation and DTE2 predictions. (9th August 2021) - Huynh, P.; Lerche, E.A.; Van Eester, D.; Garcia, J.; Johnson, T.; Ferreira, J.; Kirov, K.K.; Yadykin, D.; Strand, P.; JET Contributors,; the EUROfusion-IM Team,
Abstract: The European transport simulator is a fusion machine simulator useful for making predictions of high-performance fusion plasmas, in particular for DT reactors. Recent developments introducing self-consistent simulations of combined RF + NBI heating schemes in which majority, minority and beam ions are simultaneously heated is documented. The predictive simulations are first validated by comparison with the experimental data on a DD JET baseline plasma. In order to prepare the next JET DTE2 experimental campaign, extrapolations of fusion performance on DT plasma from DD plasma are made with a particular focus on ion cyclotron resonance heating (ICRH) computation. Traditional ion cyclotron range of frequency heating models do not permit the study of Coulomb collisional interaction of various ion species simultaneously including neutral beam injection ions, and generally forces one to consider only minority populations. Accounting for multi-population interaction is made possible here by solving coupled sets of Fokker–Planck equations for all ion species adopting the non-linear collision operator for arbitrary distribution functions, accounting for effects, such as the self-collisions of majority (or large minority) populations. To answer the question whether H minority scheme or 3 He minority ICRH scheme is better for boosting the DT fusion performance, minority concentration scans are produced.